Ancient methods of poisoning - SonaliBaliram Gaikwad (International Journal of Pharmacy and Analytical Research, 2022)
Visha (Poison) is a substance which after entering the body disturbs natural and Physiological functions of the body (i.e. Dosha, Dhatu and Mala) and it also degrades the health of the human being and which result in destructions of life. The substance immediately after entering into the body causes the vitiation of the healthydhatus or killing of the healthy person is defined as visa. Whatever substance, after entering into the body, creates panic in the normal functions of the basic tissues, destroys the wellb eing and threatens the life is called as poisons. Derivatives of Visha is explained differently by different Acharyas depending upon their aim and areas of interest. Acharyas have defined different methods of poisoning under the heading of Vishadana Adhishthana. Achryas have also mention detail treatment for it. In modern time these methods of poisoning are relevant and influences human life.